2011
DOI: 10.1097/iae.0b013e31821801c5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Choroidal Thickness Among Patients With Healthy Eyes, Early Age-Related Maculopathy, Neovascular Age-Related Macular Degeneration, Central Serous Chorioretinopathy, and Polypoidal Choroidal Vasculopathy

Abstract: The choroid was thicker in eyes with polypoidal choroidal vasculopathy or central serous chorioretinopathy than in control or age-related maculopathy groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
156
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(175 citation statements)
references
References 16 publications
8
156
2
9
Order By: Relevance
“…Consistent with some previous reports, 26,27 we have recently observed decreased choroidal thickness among patients with typical soft drusen, subretinal drusenoid deposits, and early-atrophic age-related macular degeneration compared with normals. 28 Cigarette smoking has been linked to many vascular alterations, including experimental evidence of altered retinal 29 and choroidal 30,31 blood flow, and endothelial reactivity.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with some previous reports, 26,27 we have recently observed decreased choroidal thickness among patients with typical soft drusen, subretinal drusenoid deposits, and early-atrophic age-related macular degeneration compared with normals. 28 Cigarette smoking has been linked to many vascular alterations, including experimental evidence of altered retinal 29 and choroidal 30,31 blood flow, and endothelial reactivity.…”
Section: Introductionsupporting
confidence: 93%
“…We have recently observed a thinner choroid in patients with signs of early AMD, which is consistent with some previous reports. 26,27 Both smoking history and the presence of early AMD are associated with the development of late AMD, including both geographic atrophy and choroidal neovascularization. 1,[8][9][10][11][12][13]32 Therefore, choroidal thickness may be an additional useful clinical variable in assessing risk of AMD progression or the development of late AMD, particularly considering its apparent anatomic association with these two well-known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Choroidal thickening was observed in eyes with CSC or polypoidal choroidal vasculopathy and choroidal atrophy was also noted in eyes with age-related macular degeneration. 6,12,13 An association between choroidal thickening and choroidal vascular hyperpermeability was reported in previous studies. 10,14 The cause of CSC development in pregnant women is not fully understood, and angiographic study is limited with respect to possible transplacental transport or lactation.…”
Section: Discussionmentioning
confidence: 53%
“…These findings are anticipated to be beneficial in clarifying the pathophysiology of various ocular diseases. 3,4 Despite advances in mechanization and research about CT, an automated measurement method based on recognition of the choroidal boundary obtained using SD-OCT has not been developed. A few recent studies have reported on the automated segmentation of choroid, whereby experienced observers with a good knowledge of the anatomical structure of the choroid as yet measured CT manually.…”
Section: Introductionmentioning
confidence: 99%